The Finnish inland fisheries system : the outcomes of private ownership of fishing rights and of changes in administrative practices - Sipponen, Matti (1999)
This thesis summarises the results of six studies describing the organisation and functioning of the fisheries system of Finnish inland waters. During the past 15 years, the efficiency of inland fisheries has been improved due to changes in fisheries legislation, in particular the establishment of regional management units, which have provided for the participation of many relevant interest groups in the decision-making process, thereby improving the practice of co-management. The outcomes of the fisheries system were found to depend more on political-administrative institutions than on biological productivity. The system shows greater stability at the lower hierarchical levels. Access to fishing grounds is of vital importance in both professional and recreational fishing. The long-run private market equilibrium supply for recreational fishing with active types of gear accounted for 50% of the Finnish lake surface area. Due to an input-oriented management policy the resource rents which should have accrued to statutory fishery associations from fishing licence sales dissipated, contradicting the predicted outcome of private ownership. The price mechanisms provided the owners with insufficient information as to what direction to take to improve the management and supply of fishing grounds. Locality turned out to be a dominant feature of recreational fishing. As regards professional fishing, state-ownership of fishing grounds was a recruitment channel into the occupation, and was also found to facilitate effective operations contrary to that of private _ownership. The social environment and the patters of behaviour of professional fishermen have remained largely unchanged in spite of the rapid technological development in the industry. Private ownership has led to a suboptimal allocation of fisheries resources, particularly in the professional branch of the industry. Within fisheries regions, an appropriate scale for management has been found which will enable managerial responsibilities to be increasingly vested in them in the future.